Vesijärven ja Tammiston aikaisen suhtautumisesta perunavirooseihin - Brummer, Veikko (Agricultural and Food Science, 1949)
The potato virus diseases have since the 30th decade of the 20th century during warm and dry growing seasons been very common in potato experiments at the Plant Breeding Station Tammisto. Especially the early varieties Harbinger, and Tammisto Early (a native improvement of a cross between Up to date and Prof. Edler) have been studied, because their susceptibility to the virus diseases was very different. Harbinger is susceptible to the streak, and therefore it will rather quickly degenerate at Tammisto. Tammisto Early again is obviously resistant, probably only tolerant to the virus diseases. The yielding capacity of the after-cultivated Tammisto Early remained nearly unchanged. This variety, however, seems to be susceptible to the Verticillium-disease.